Hybrid MPC-Based Automatic Generation Control for Dominant Wind Energy Penetrated Multisource Power System. (17th January 2022) - Hasan, Naimul; Alsaidan, Ibrahim; Sajid, Mohammad; Khatoon, Shahida; Farooq, Shuaib
Abstract : This paper presents hybrid model predictive control-based automatic generation regulator design for dominant wind energy penetrated multisource power system. The other power generation sources hydro and thermal are also considered in each area. The proposed AGC regulator is designed for each independent area considering only local power system states to ensure the stability of closed-loop system under small perturbation. The performance of the proposed AGC regulator has been validated for 2% step load perturbation. Furthermore, system parameter is varied to 20% of nominal value to assess the robust performance of the regulator. Performance evaluation between the hybrid MPC, conventional MPC, and traditional AGC regulators considering the dominant participation of the DFIG wind turbines is presented to demonstrate the superior performance of the hybrid MPC AGC regulator.